Les enjeux de la traduction en tant que pratique d’écriture et opération éditoriale : la mise en disponibilité de la Corografia Brasílica (1817) par la presse française en 1821 - Rafael Souza Barbosa (Les Cahiers de Framespa)
This article focuses on translation as social writing practice by analyzing the French translations of Corografia Brasílica, ou Relação Histórico-Geográfica do Reino do Brasil (1817), by Manoel Aires de Casal (1754-1821), published by the Journal des Voyages, ou Archives Géographiques du xixe siècle and by the Nouvelles Annales des Voyages, de la Géographie et de l’Histoire in 1821. Our analysis relies on the material and symbolical circumstances allowing the production of these translations and points out the actions of the social actors involved. It aims at comprehending the economy of their actions, a major historical issue, by an empirical microanalysis of writing and publishing practices. Thus, it allows a better approach of the multiscale mechanisms behind making writings available and the collaborative intellectual practices. We argue that we can determine new possibilities made available for the production of historical knowledge when considering written objects as written practices in loco; and when trying to understand from what is left of intellectual practices what agents have actually done with written pieces and by writing.